The cultural dimension of Knowledge Organization: an analysis in the Information Science international context - Chaves Guimaraes, Jose Augusto [UNESP]; Evangelista, Isadora Victorino [UNESP]; Medeiros Luz, Gabriele de Araujo [UNESP]; Osawa, Henrique Fiamengue [UNESP] (Univ Zaragoza, 2019)
The studies on the cultural dimension of the knowledge organization have been getting a prominent role in scientific communications, revealing their importance in the current academic context. The investigations in epistemic communities can help in the study of this topic in evidence, identifying its main theoreticians and sources of information, in order to help the development of future researches. It was possible to identify a strong theoretical contribution in researchers working in Brazil, as well as prominent research sources in the ISKO context and periodicals such as Scire. In conclusion, it was possible to identify a community that contributes in a profitable way to the area and that can serve as a basis for the construction of new knowledge about the cultural aspects of knowledge organization.
Keywords: Knowledge Organization; Cultural dimension; Epistemic communities